PROBLEM OF SUCCESSION TRAINING INFORMATION TECHNOLOGY IN SCHOOL AND HIGHER EDUCATIONAL ESTABLISHMENT (Journal of Information Technologies in Education (ITE), 2013)
Problem caused by the contradiction between the current requirements for the results of the teachers training in teacher training institutions and the level of formation of IT competencies of applicants in article considers.
Keywords: information technology; education system; student; future teacher; foreign language; school; personality